Identification of the discharge kinetics in the perfluoro-nitrile C4F7N with swarm and breakdown experiments. (27th March 2019) - Hösl, Andreas; Chachereau, Alise; Pachin, Juriy; Franck, Christian M
Abstract: We follow up on our previous publication on C4 F7 N and investigate the ion kinetics influencing C4 F7 N discharges with a pulsed Townsend experiment. The measured current signals at pressures between 0.06 and 6.9 kPa, in the range of density-reduced electric fields E / N from 500 to 1050 Td, show evidence of three anions: one long-lived anion with a detachment rate coefficient in the order of, a presumably non-detaching anion, and a short-lived anion with a detachment rate coefficient in the order of . We obtain the corresponding rate coefficients for ionization, attachment and detachment in C4 F7 N. Using these results, we calculate a corrected value of the effective ionization rate coefficient, taking into account detachment from negative ions. It results in a corrected value of the density-reduced critical electric field strength Td, much lower than the previously obtained value of Td, which is valid only when electron detachment is negligible, i.e. for low pressure and small geometric distance. To find which value is most relevant for electrical insulation, we perform breakdown voltage measurements in homogeneous electric fields in C4 F7 N at 5–65 kPa. We compare the measured density-reduced breakdown field strength to that calculated using the streamer criterion with the presently obtained rate coefficients, including electron detachment. We find excellent agreement between the measured and calculated .